2014
DOI: 10.1080/22311866.2014.936900
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Total Phenolic Contents and Antioxidant Activity ofSyzygium caryophyllatumandSyzygium densiflorum

Abstract: To search the new sources of antioxidants, leaves of Syzygium caryophyllatum and Syzygium densiflorum were screened for total phenolics and antioxidant activity. The leaves of the plants were extracted with hexane, ethyl acetate and methanol, and screened for their phytochemicals, phenolic content (TPC), and flavonoid content (TFC) and antioxidant activity. Phytochemical analysis of the both plants revealed the existence of flavonoids, tannins, glycosides, terpenoids and protein. Phenolic and flavonoid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A previous study on DPPH radical scavenging activity of the S. caryophyllatum leaves has reported DPPH inhibition activity in methanol extract with 81.97%, followed by EA (78.69%) and Hex fraction (34.34%) at the concentration of 100 μ g/mL [ 14 ]. Annadurai et al [ 31 ] have reported DPPH scavenging activity for the EA fraction of S. caryophyllatum leaves as 86.14% inhibition at a concentration of 400 μ g/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study on DPPH radical scavenging activity of the S. caryophyllatum leaves has reported DPPH inhibition activity in methanol extract with 81.97%, followed by EA (78.69%) and Hex fraction (34.34%) at the concentration of 100 μ g/mL [ 14 ]. Annadurai et al [ 31 ] have reported DPPH scavenging activity for the EA fraction of S. caryophyllatum leaves as 86.14% inhibition at a concentration of 400 μ g/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Annadurai et al [ 31 ] have reported DPPH scavenging activity for the EA fraction of S. caryophyllatum leaves as 86.14% inhibition at a concentration of 400 μ g/mL. Subramanian et al [ 14 ] and the present study show similar results for the EA fraction with a value of 72.92% inhibition at the concentration of 150 μ g/mL. A previous study carried out by sequential extraction method for leaves and fruits has reported having IC 50 value for DPPH scavenging activity in methanol as 34.9 ± 1.2 μ g/mL and 69.4 ± 0.7 μ g/mL, respectively, which showed high activity compared to the present study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamun contains magnesium, iron, manganese, calcium, copper, zinc, phosphorus, potassium, nitrogen, and sulfur as micronutrients. [16][17][18][19][20][21][22][23] Flavonoids, terpenoids, tannins, and carbohydrates have been detected in the ethanol extract of Jamun leaves whereas carbohydrates were detected in the chloroform, ethyl acetate, and methanol extracts. 24 Acetone extract of Jamun leaves possessed glycosides, phenols, saponins, proteins, and resins whereas stem bark extract contained alkaloids and flavonoids.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Comparable results were obtained previously with S. caryophyllatum and S. densiflorum and endemic Eugenia species. (Subramanian et al, 2014;Eshwarappa et al, 2014;Brunchault et al, 2014).…”
Section: Total Flavonoid Contentmentioning
confidence: 99%